Amministrazione penitenziaria, Volontariato, Terzo Settore (Società e diritti, 2023)
The paper analyzes the role of the third sector in the context of the prison administration. Starting from the origins, passing through the debate in the constituent assembly, the paper retraces the evolution of legislation that has recognized an ever greater space for the intervention of voluntary work that the third sector can bring about. As this is a moment of great regulatory ferment, in the light of some recent reforms, including the so-called Cartabia Reform, the paper stresses the risks and potential of the third sector in a particular context such as that aimed at ‘welcoming’ - in symbolic and practical terms - those who are deprived of personal freedom. The constitutional framework, in particular, the principles of solidarity, of equal dignity, the personalist principle and the re-educational finalism, confirm for an ever greater space of the third sector in the penitentiary context, without prejudice to the need to mark a distance from the roles and functions of the public administration, as to avoid that the conspicuous inefficiencies in the treatment services are not visible.